Synergistic Effect of Berberine-Based Chinese Medicine Assembled Nanostructures on Diarrhea-Predominant Irritable Bowel Syndrome In Vivo - Li, Lei; Cui, Herong; Li, Tong; Qi, Jinchai; Chen, Hongshan; Gao, Feng; Tian, Xuehao; Mu, Yunnong; He, Rui; Lv, Siyuan; Chu, Fuhao; Xu, Bing; et al. (Frontiers in Pharmacology, 2020)
Diarrhea-predominant irritable bowel syndrome (IBS-D) is one common chronic functional disease of the digestive system with limited treatments. The microbiota–gut–brain axis (MGBA) has a central function in the pathogeny of IBS-D, which includes the participation of many various factors, such as brain-gut peptides (BGPs), immune inflammation and intestinal flora. Inspired by the drug combination in traditional Chinese medicine (TCM), our previous study discovered that BBR and BA could form natural self-assemblies as BA-BBR nanoparticles (BA-BBR NPs) and showed synergistic effects against IBS-D. Here, we investigated the synergistic effects of BA-BBR NPs on IBS-D model mice induced by chronic restraint stress plus senna decoction with the influence on MGBA. BA-BBR NPs showed the better therapeutic effect on improving visceral hypersensitivity and diarrhea on IBS-D model mice, compared with BBR, BA, and BA/BBR mixture. Furthermore, BA-BBR NPs significantly (P<0.05) reduced the levels of 5-hydroxytryptamine (5-HT), vasoactive intestinal polypeptide (VIP) and choline acety transferase (CHAT) in colon tissues or of serum from BGPs; it lowered the expressions of the nuclear factor kappa-B (NF-κB) in colon tissues and changed the levels of basophil granulocyte (BASO) and leukomonocyte (LYMPH) in whole blood from immune inflammation; it altered the intestinal flora of Bacteroidia, Deferribacteres, Verrucomicrobia, Candidatus_Saccharibacteria and Cyanobacteria from intestinal flora. In conclusion, BA-BBR NPs, after forming the natural self-assembly between BBR and BA, promoted the synergistic effect on IBS-D mice than the sum of BBR and BA effects, based to the formation of self-assemblies rather than the simple mixing. It further proved that synergistic effect of BA-BBR NPs on IBS-D mice might be related to BGPs, immune inflammation and intestinal flora from three important interrelated components of MGBA. This study will provide a novel idea for the interpretation of TCM compatibility theory and provide the basis for BA-BBR NPs as a natural and efficient nanomaterial for clinical use.